Analysis Of Self-Concept And Self-Independence In The Behavior Of Disabled Group Who Perform Plastic Waste Recycle Business - Afrie Sweet Chris Deny Ekasari; Sandu Siyoto; Ema Mayasari (Journal of Global Research in Public Health, 2018)
The loss of one or more parts of a physical body that cannot function properly can affect a person's psyche and psychology, allowing a negative self-concept to arise. The purpose of this study was to determine the Influence of Self-Concept and Self-Independence on the Behavior of Disabled Groups Who Conduct Plastic Waste Recycling Businesses. The research design is cross-sectional study, respondents were taken using the Simple Random Sampling technique. The population of all people with disabilities is 74 people, the sample is 61 respondents. Independent variables are self-concept and self-independence in people with disabilities, dependent variables are recycling behavior of plastic waste, the results are analyzed using the Ordinal Regression test. The results of the study showed that the majority of respondents had a good self-concept, namely 33 respondents (54.1%), the majority of respondents were independent in carrying out activities, namely 42 respondents (68.9%), almost half of the respondents had good behavior in carrying out activities.recyclerubbishwhich is 29 respondents (47.5%). The results of the statistical test show a p value = 0.020 for self-concept so that H1 is accepted which means that there is an influence of self-concept on the behavior of groups of people with disabilities who carry out plastic waste recycling efforts and a p value = 0.030 for self-independence so that H1 is accepted which means that there is an influence of self-independence on the behavior of groups of people with disabilities who carry out plastic waste recycling efforts. Self-concept and self-independence influence the behavior of groups of people with disabilities who carry out plastic waste recycling efforts, where the higher the self-concept and the more independent people with disabilities are in carrying out activities, the better the behavior of carrying out plastic waste recycling efforts.